Pelaksanaan Model Kooperatif dalam Pembelajaran Sepak Bola di Kelas XI MAN 2 Karawang - Irham Sha Ghira; Abduloh Abduloh; Evi Susianti (Jurnal Ilmiah Wahana Pendidikan, 2022)
In this study, it aims to find out how the implementation of cooperative model in soccer learning in class XI MAN 2 Karawang. The approach used in this study is a qualitative approach with a qualitative descriptive method. The subject in this study is the population class XI students from each class 2 people as representatives of 5 classes, so the subjects involved consisted of 10 students and 1 eye teacher corner lesson, sampling using simple random technique example. In this study, the researcher used the instrument itself by using data collection techniques, namely, observation, interviews, and documentation. The results of this study show the process of implementing the model cooperative learning in soccer learning in class XI MAN 2 Karawang walking well, effectively and smoothly, this is evidenced by 9 respondents getting maximum results in learning